2021
DOI: 10.1108/cg-12-2020-0575
|View full text |Cite
|
Sign up to set email alerts
|

Does board gender diversity affect capital structure decisions?

Abstract: Purpose The purpose of this paper is to investigate the indirect relationship between board gender diversity and capital structure decisions and to examine whether the capital structure is affected by the type of approach used to promote women’s participation in the boardroom. Design/methodology/approach Based on a sample of French non-financial listed companies over the period 2006–2019, this paper uses structural equations modeling, difference-in-differences using propensity score matching and chow test to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Furthermore, Menicucci and Paolucci (2022), Hurley and Choudhary (2020), Faccio et al (2016) and Huang and Kisgen (2013) documented that companies with a diverse executive level (especially board) are significantly more risk-averse. Related research by Ben Saad and Belkacem (2022) found that BGD affects capital structure decisions through this risk-taking channel. Chatjuthamard et al (2021) investigated the relationship between BGD and hostile takeover vulnerability and found a negative association between them.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Furthermore, Menicucci and Paolucci (2022), Hurley and Choudhary (2020), Faccio et al (2016) and Huang and Kisgen (2013) documented that companies with a diverse executive level (especially board) are significantly more risk-averse. Related research by Ben Saad and Belkacem (2022) found that BGD affects capital structure decisions through this risk-taking channel. Chatjuthamard et al (2021) investigated the relationship between BGD and hostile takeover vulnerability and found a negative association between them.…”
Section: Literature Reviewmentioning
confidence: 94%
“…The first step is to measure the four characteristics of director efficacy individually, and these are based on the following metrics: Director independence is the ratio of independent and non-executive directors to the total number of the members of BoD (Bhat et al , 2018; Raimo et al , 2022; Nikulin et al , 2022). Female director representation is the percentage of female directors on corporate boards (Terjesen et al , 2016; Proenca et al , 2020; Saad and Belkacem, 2021). Director remuneration is the compensation the firm pays to BoD.…”
Section: Methodsmentioning
confidence: 99%
“…Female director representation is the percentage of female directors on corporate boards (Terjesen et al , 2016; Proenca et al , 2020; Saad and Belkacem, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The independent variable consists of two sets of variables. The first set includes several CG mechanisms, namely, block ownership (Kaur and Gill, 2009), ownership concentration (Luo, 2015; Ben Saad and Belkacem, 2022), outsider blockholder (Core et al , 1999), board size (Ullah et al , 2019; Agyei-Mensah, 2022; Menicucci and Paolucci, 2022), board independence (Agyei-Mensah, 2021; Aladwey et al , 2022; Chatjuthamard et al , 2022; Gupta and Mittal, 2022) and CEO duality (Ghosh, 2006; Aldogan Eklund, 2022; Khan, 2022). The ownership variables block ownership and ownership concentration aids in estimating the distribution of power between large and minority shareholders (Kaur and Gill, 2009), whereas outsider blockholder capture the influence of the external type of blockholder on the COMP decision (Boone et al , 2011).…”
Section: Methodsmentioning
confidence: 99%